Integrating Equity and Reconciliation Work into Archival Descriptive Practice at the University of Waterloo - Robichaud, Danielle (Archivaria, 2021)
Despite sustained calls for a critical review of harmful content within archival descriptive records, there remains much to be explored by way of implications for Canadian academic archives. This article addresses the absence of Canadian archival practitioners in broader discussions about the revision and remediation of descriptive records by exploring how staff in Special Collections & Archives at the University of Waterloo Library are working to integrate equityand reconciliation-informed thinking into the department’s archival practice by revising their approach to language in archival descriptions. Beginning with an overview of the department and the landscape in which it operates, this article provides a brief review of guidance available in the Rules for Archival Description. It then provides the rationale behind the recent changes to descriptive practice before exploring a series of examples of how and where this work is newly underway. The article concludes with a consideration of current identified challenges and the related work ahead. RÉSUMÉ Malgré les appels répétés pour une revue critique du contenu blessant dans les descriptions d’archives, il reste beaucoup à explorer en termes de ce que cela signifie pour les archives universitaires canadiennes. Cet article aborde l’absence des archivistes praticiens canadiens dans les discussions générales autour de la révision et de la réhabilitation des notices descriptives en explorant comment le personnel des Collections spéciales et des Archives à la Bibliothèque de l’Université de Waterloo travaille à intégrer une pensée tenant compte de l’équité et de la réconciliation dans les pratiques archivistiques du département en revisitant leur approche au langage dans la description archivistique. Commençant par un survol du département et du décor dans lequel il opère, l’article offre un bref aperçu des directions disponibles dans les Règles pour la description des documents d’archives. Il fournit ensuite les raisons sous-jacentes aux récents changements dans les pratiques descriptives avant d’aborder une série d’exemples illustrant comment et où ce travail est en cours depuis peu. Cet article se termine en se penchant sur les défis actuels et le travail à venir pour leur répondre.